2010
DOI: 10.1111/j.1530-0277.2010.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of GABRA2 in Moderating Subjective Responses to Alcohol

Abstract: Background Human twin studies have shown that certain responses to alcohol, including subjective perceptions, are genetically influenced. Previous studies have provided evidence that a low level of response to alcohol predicts future alcohol use disorders in humans. Recent genetic studies suggest an association between alcohol dependence and genetic variation in the γ-aminobutyric acid A (GABAA) receptor α2 subunit gene (GABRA2). Based on a haplotypic association of alcohol dependence with GABRA2, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 54 publications
2
35
0
2
Order By: Relevance
“…The results of the earlier study also contrast with other more recent reports that GABRA2 alleles, which are overrepresented in alcohol dependence subjects, were associated with a greater “high” following alcohol administration (Kareken et al 2010; Arias et al 2014). The lack of a GABRA2 genotype×alcohol interaction on BAES stimulation and sedation subscales reported herein is consistent with the lack of GABRA2 genotype moderation of alcohol effects on the BAES reported by three other groups examining moderately large samples (Haughey et al 2007; Roh et al 2011; Uhart et al 2013). …”
Section: Discussionsupporting
confidence: 90%
“…The results of the earlier study also contrast with other more recent reports that GABRA2 alleles, which are overrepresented in alcohol dependence subjects, were associated with a greater “high” following alcohol administration (Kareken et al 2010; Arias et al 2014). The lack of a GABRA2 genotype×alcohol interaction on BAES stimulation and sedation subscales reported herein is consistent with the lack of GABRA2 genotype moderation of alcohol effects on the BAES reported by three other groups examining moderately large samples (Haughey et al 2007; Roh et al 2011; Uhart et al 2013). …”
Section: Discussionsupporting
confidence: 90%
“…Two subsequent studies in the COGA dataset have shown that the original evidence for association with AUD derived only from individuals with comorbid illicit drug dependence [48] and in adolescents, GABRA2 is associated with childhood conduct disorder symptoms, known to be a predictor of later-onset AUD [49]. Furthermore, GABRA2 variation appears to influence the subjective response to alcohol [50] and an fMRI study using a monetary incentive delay task has shown that GABRA2 variation is probably associated with impulsivity through variation of insula activity responses [51]. …”
Section: Strategies For Identifying Genetic Associations With Alcoholismmentioning
confidence: 99%
“…In human brain imaging studies, a persistent down-regulation of central GABA A Rs in early abstinence was demonstrated [52][53][54] . One hundred and ten healthy social drinkers (53 men) in a drinking study showed that the GABRA2 gene is associated with subjective (pleasant or unpleasant sensations) effects of alcohol, suggesting that GABRA2 may play a role in the risk of developing alcohol use disorders by moderating the subjective effects of alcohol [55] . However, the neurobiological basis by which genetic variation and in which brain region translates into alcohol dependence is largely unknown.…”
Section: Underlying Mechanisms Of Audmentioning
confidence: 99%